Digitalisierung in der Grundschule Grundlagen, Gelingensbedingungen und didaktische Konzeptionen am Beispiel des Fach Sachunterrichts - Haider, Michael; Schmeinck, Daniela (Verlag Julius Klinkhardt, 2022)
Using the example of the multi-perspectival subject of science education, the book shows the basics, conditions for success and didactic concepts of digitization in elementary school. It describes the various aspects of digitization in elementary schools and provides a sound basis for political, pedagogical and didactic discourse. The book focuses not only on fundamental theoretical considerations of digital education in science education, but also on selected aspects of individual support with and through digital media, as well as on concrete suggestions for action and implementation options for digitization in science education. In this sense, the book offers suggestions for theory, research and practice.